Population Development and Improvement of Education Infrastructure in Riau Province: A Case Study at the Regional Office of the Ministry of Religion in Riau Province - Harmendra; Hamdi (AMUYA: JOURNAL OF MANAGEMENT, 2025)
The population growth in Riau Province is increasing every year. This is in contrast to the existing educational infrastructure. Furthermore, the interest of students and parents in continuing education in Madrasah is also increasing. However, the growth rate of madrasah educational units seems to experience stagnation or zero growth. Therefore, this study aims to map the population growth in Riau Province and the available educational infrastructure for madrasah. This is important to achieve equal education as mandated by the law and to support the achievement of the Excellent and Dignified Riau Province Vision 2019-2024. The conclusion of this study provides a recommendation for the Regional Office of the Ministry of Religion in Riau Province to create a program for the establishment of madrasah at the district/city level. Furthermore, the equal distribution of educational infrastructure is also important to be one of the priority policies to achieve the National Education goals effectively.